Annual Plan 1964-65 (Memoranda) Jammu and Kashmir State - Planning Commission (Planning Commission, 1963)
In the Memoranda submitted with the Annual plan for 1969-63 it was stated that " the State Government have had a second look at these proposals and they have decided that greater emphasis should be placed on Power schemes and schemes relating to large and Medium Industries. They have also further decided that in the field of industrialization the Government should invite private parties to collaborate with them. Some effective steps to implement these decisions have already been taken.
Planning Department, Jammu and Kashmir State